Efficient Biometric Authentication Technique Using the Gray scale Information’s of Sclera, Iris and Pupil - et. al., P.Rajasundaram, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The motive of this research is to accomplish a secure enhanced biometric authentication system by using the gray scale information’s of Iris and Pupil. The gray scale values are in the range of 0-255 depending upon the colors of image before they converted as gray scale image. The Iris feature in an eye image has a lot of different structural patterns and these structural patterns will be distinguished by the difference in gray scale information’s. The gray scale information’s will clearly show the difference in the iris and pupil structural feature even the difference is very small. So the author preferred to use the gray scale value for a secure enhanced biometric authentication system. The proposed work is divided as (i) Image acquisition (ii) Preprocessing (iii) Finding iris length (iv) Creating templates (v) Creating stored templates and (vi) Feature Matching. The iris length is found out by using the gray scale information’s appeared in the interfacial layer of sclera and iris. The required templates are created by using the gray scale information’s from the specific row and column. During the execution the wrong matches will be rejected with in short time by comparing with iris length. If the iris length is matched well then the template matching process will be carried out. It will take appropriate time while the exact match enters in to the comparison. Finally the proposed work gives 99.88% accuracy with high performance.